Moorrees-like mesh diagram for Romanian patients - a pilot study - Cornea, Daniela; Decusara, Mioara; Dolea, Gicuta; Nicolau, Alexandru Mircea (Medicine and Pharmacy Reports, 2020)
diagrams to ease the orthodontic diagnosis and treatment of North-American patients. Subsequently, the system was adapted by different authors to other races and populations. The objective of this study is to provide a system of Moorrees-like mesh diagrams for the Romanian population, Caucasian race, which would help orthodontists, surgeons and prosthetists. Methods. 40 patients were introduced in the study, 20 males and 20 females, with ages between 12-33 years, permanent dentition and slight dental-maxillary abnormalities, class I and II Angle. For each patient, a lateral cephalometric radiograph was taken, with CRANEX 3D, head straight, maximum intercuspation. On tracing paper were drawn 35 anthropometric points and 3 planes, Frankfurt plane, as the horizontal landmark, a perpendicular line through nasion as the vertical landmark and the occlusal plane. From each point we measured the distance in millimeters to the horizontal landmark and to the vertical landmark, respectively. The obtained values were introduced into 40 tables, using Microsoft Office Excel 2007 and 3 arithmetic means were calculated, for males, for females and a general one, for children under 12 years old. The arithmetic means were transferred on millimetric paper and tracing paper, joining the obtained points and completing the templates. Results. Three different Moorrees-like mesh diagrams were obtained, one for male, one for female and a mixt one for children under 12 years, Romanian patients, Caucasian race, respectively. Conclusions. Mesh diagram comes in the support of a better perspective of the anatomical elements of the face and the facial growth, being a useful tool in predicting treatment. Computer based programs with Moorrees-like diagrams adapted to Romanian patients may be the object of further studies.